Perancangan Sistem Informasi Penjualan dan Pembelian Merchandise Darjofans Berbasis Website - Darmawan, Dikky Putra; Rahmawati, Yunianita; Rosid, Mochamad Alfan (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Darjofans Merchandise is a store that offers various Deltras and Deltamania attributes. The sales system at Darjofans Merchandise is still conventional so that customers are required to come to the store to make purchases and the marketing reach used by Darjofans Merchandise is lacking. To overcome these problems, this research will design an information system for selling and purchasing Darjofans merchandise based on a website so that customers who want to buy products only need internet access without having to go to the store and customers can receive up to date information and will use the waterfal method as software development methods. And data collection techniques used are observation, interviews, and literature study. And the results of the research that has been done is that the sales and purchase information system helps shop owners to make it easier for customers to know the products being sold and buy these products without having to visit the store. This information system will also be equipped with an online payment system that is integrated with Midtrans as a payment gateway service provider so that the transaction process becomes faster, easier and more practical